Ethical Democracy: An Analysis Of The Ethicality Of Post-Reform Election Organizers From The Perspective Of Historical Instit`Utionalism - Ibrahim Ibrahim; Iman Cahyanto (Journal of Government and Politics (JGOP), 2026)
The phenomenon of ethical violations by election organizers in post-reform Indonesia has intensified, extending to regional and city-level election organizers. From 2012 to 2024, the Election Organizer Honorary Council (DKPP RI) recorded 5,670 complaints of ethical violations against the General Elections Commission (KPU) and the Elections Supervisory Agency (Bawaslu). This high rate of ethical violations has created a decline in modern substantive democracy. Ethical violations by election organizers post-reform are not simply individual deviations, but rather the result of structural vulnerabilities created by institutional design, power configurations, and electoral political incentives. A case study from 2025 revealed that the DKPP RI imposed a strict sanction of dismissal on a member of the Bogor City KPU after being found guilty of using his authority for transactional gain, seeking the favor of one of the Bogor mayoral candidates. This study explains that ethical violations by election organizers are the result of a structural configuration between institutional design, electoral political incentives, and oligarchic pressure. The method used is descriptive analysis, a research method that focuses on current and ongoing solutions by collecting and compiling data, which is then analyzed to find answers. This research seeks to contribute to strengthening the electoral system and democracy in Indonesia by using a historical institutional approach to interpreting ethical violations of election officials in Indonesia. Therefore, this research seeks to examine the recruitment process of election officials in Indonesia after the reform era and analyze the phenomenon of structural and recurrent ethical violations.